ChemInform Abstract: Organic Synthesis Enabled by Light‐Irradiation of EDA Complexes: Theoretical Background and Synthetic Applications. Issue 18 (April 2016) - Lima, Carolina G. S.; de M. Lima, Thiago; Duarte, Marcelo; Jurberg, Igor D.; Paixao, Marcio W.
Abstract: Review: 167 refs.